THE DIGITAL DIVIDE BETWEEN X AND Y GENERATION IN A GOVERNMENT PROVINCE OF DKI JAKARTA - Ninda Putti Arrochmah; Kharisma Nasionalita (Mediakom, 2020)
This research measures the digital divide index between X and Y generation in civil servants in DKI Jakarta Province. The subvariables of the digital divide that measured in this research are: 1) Internet Usage Behavior; 2) The Advantage of Internet; 3) Usage Divide; and 4) Quality of Use Divide. This study uses quantitative methods with data collection techniques through surveys involving 100 respondents who have been randomly selected. Sampling using a gradual cluster technique. The data analysis technique used the Mann Whitney test to determine the comparison of the value of the digital divide between the two groups of research subjects. The result shows that the mean rank value of generation Y was superior in each sub variable compared to generation X. Nevertheless, the digital index values in the two generations are considered low. Among of these four subvariables, the highest gap between these two generations is the Usage Divide which refers to internet usage skills gap between people who have access to the internet.